Influence of the Rootstock on the Ability of Stark Rimson Apple Cultivar on N, P, and K Mineral Uptake under Rainfed Conditions in Sweida Province (Damascus University Journal of agriculture sciences, 2021)
The research was conducted at the Pome and grapevine Division and agricultural scientific research center fields and laboratories in Sweida- GCSAR during 2011-2012 to study the influence of apple rootstocks (Malus domestica and MM106) on N, P and K minerals uptake in Stark Rimson cultivar under rainfed conditions. The results showed that thehighest significant accumulation of Nitrogen, Phosphorous and Potassium   in shoots were in May for the two studied rootstocks in the comparison with other growth months, which were 2, 0.22, and  0.78% respectively in MM106 rootstock, while they were 1.6. 0.22, and 0.79% respectively in Malus domestica rootstock. In leaves, the significant accumulation of N  was at the end of June for the two rootstocks in comparison with the other growth months, and MM106 significantly revealed higher accumulation of Nitrogen than Malus domestica  (2.9% and 2.7%, respectively),while forP and K elements, the highest accumulation was in may in trees which grafted on MM106 rootstock which were 0.26 and 1.35, respectively, and the trees that grafted on Malus domestica rootstock significantly revealed the highest accumulation in August (1.57%). In fruits, the